(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article discusses the importance of English as a global language, exploring its historical development, role in business, science, education, and diplomacy. It also examines the challenges associated with English as a dominant language and its impact on linguistic diversity.